2013
DOI: 10.1007/s00467-013-2420-0
|View full text |Cite
|
Sign up to set email alerts
|

Correspondence between Ca2+ and calciuria, citrate level and pH of urine in pediatric urolithiasis

Abstract: BackgroundHypercalciuria and hypocitraturia are considered the most important risk factors for urolithiasis. Citrate binds to urinary calcium to form a soluble complex which decreases the availability of ionized calcium (Ca2+) necessary for calcium oxalate formation and phosphate crystallization. The aims of this study were to assess the Ca2+ fraction in relation to total calciuria, citraturia and urinary pH and to determine whether urinary Ca2+ concentration is a helpful biomarker in metabolic evaluation of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…Conversely, alkalosis increases citrate excretion. The definition of hypocitraturia is ill‐defined, with some proposing absolute excretion cut‐off and others using calcium/citrate, citrate/calcium, and citrate/creatinine ratios . As hypercalciuria is an important comorbidity of hypoparathyroidism and its therapy, we chose to focus on the UCa/Ucit ratio, with the understanding that the risk for renal calcification is more likely related to the relative concentrations of these two analytes, rather than their absolute excretion.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, alkalosis increases citrate excretion. The definition of hypocitraturia is ill‐defined, with some proposing absolute excretion cut‐off and others using calcium/citrate, citrate/calcium, and citrate/creatinine ratios . As hypercalciuria is an important comorbidity of hypoparathyroidism and its therapy, we chose to focus on the UCa/Ucit ratio, with the understanding that the risk for renal calcification is more likely related to the relative concentrations of these two analytes, rather than their absolute excretion.…”
Section: Discussionmentioning
confidence: 99%
“…Many authors have postulated that not only the absolute urinary calcium or citrate concentrations, but alternatively the relative proportion of the two, determine the risk of stone formation [ 20 , 25 , 26 ]. It has been shown that a urinary calcium/citrate index of 0.326 mg/mg can discriminate well between pediatric stone formers and healthy controls [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another aspect of our study was to examine the correspondence between Ca 2+ and/or calciuria in pediatric diseases. Recent data indicate increased Ca 2+ concentration in stone-formers [ 28 ]. The urinary concentration of Ca 2+ is largely pH-dependent.…”
Section: Discussionmentioning
confidence: 99%